PERAN LINGKAR GANJA NUSANTARA DALAM LEGALISASI GANJA - Satya Parama, I Dewa Made; Ranteallo, Ikma Citra; Kebayantini, Ni Luh Nyoman (JURNAL ILMIAH SOSIOLOGI (SOROT), 2015)
ABSTRACT Lingkar Ganja Nusantara (LGN) is the first organization that fought in realizing the legalization of marijuana in Indonesia. The paper examined which extent the organization’s role in realizing the idea of ??legalizing marijuana and how their strategies in changing social construction of marijuana. In this paper I draw 14 informants in-depth interviews including 5 key informants as LGN members in Bali and 9 informants from BNNP Bali, marijuana users and non-users. The concept of Talcott Parsons’ structural functionalism, social construction and deviance to shed light on three important roles in realizing the legalization of marijuana form LGN Dewata including assessment, education and regulation. The changing of social construction on marijuana by LGN strategies are increasing education and knowledge of mariuana itself, promoting the brand and products of LGN, and giving benefits information of marijuana widely over the Internet. Keyword: Lingkar Ganja Nusantara, Lingkar Ganja Nusantara Dewata, Legalizing Marijuana, Social Construction.